2008
DOI: 10.1002/dat.20274
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Complications Following Living Donor Nephrectomy

Abstract: BACKGROUNDThe aim of this study was to highlight unusual complications following living‐donor nephrectomy within a single center.METHODSBetween January 2003 and February 2008, 58 donor nephrectomies (52 open and 6 laparoscopic hand‐assisted) were performed. All donors were followed up at 6 weeks and then discharged to regular yearly visits with their designated nephrologists. All complications were entered prospectively into a database used for this analysis.RESULTSForty‐four (76%) had a left donor nephrectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Bleeding constitutes a major risk in living donor nephrectomies as is further observed in a study conducted by Akoh et al . [ 8 ] In this study, among 58 patients, 4 (7%) of the patients had bleeding requiring postoperative transfusion. Most of the patients underwent open nephrectomy 89% and only 11% laparoscopic.…”
Section: Discussionmentioning
confidence: 70%
“…Bleeding constitutes a major risk in living donor nephrectomies as is further observed in a study conducted by Akoh et al . [ 8 ] In this study, among 58 patients, 4 (7%) of the patients had bleeding requiring postoperative transfusion. Most of the patients underwent open nephrectomy 89% and only 11% laparoscopic.…”
Section: Discussionmentioning
confidence: 70%
“…Of note, in the study by Gjerston et al, While minor and self-resolving testicular pain may be just a nuisance, in some cases it may prove problematic. Akoh et al reported a case of a donor who had unrelenting testicular pain following right nephrectomy and eventually required an orchidectomy for symptomatic control (7). Felix et al also reported a donor who required orchiectomy in their analysis of post-operative complications from the Swiss Organ Living Donor Health Registry (8).…”
Section: Discussionmentioning
confidence: 99%